2018
DOI: 10.1590/1806-93042018000300004
|View full text |Cite
|
Sign up to set email alerts
|

Inevitable mother-baby separation in the immediate postpartum from a maternal perspective

Abstract: Objectives: to understand the process of inevitable mother-baby separation in the immediate postpartum from a maternal perspective. Methods: this is a qualitative approach research study developed by interviewing 15 mothers who were separated from their children in the postpartum at a public maternity hospital in Belo Horizonte, Minas Gerais, Brazil. The analysis content was used for data interpretation. Results: the categories were evidenced through "Maternal feelings and perceptions regarding to the child'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…Separation between the mother and the newborn may create insecurity and unnecessary worrying for the mother and delay the bonding and breastfeeding initiation. Studies have also revealed separation as a cause for stressors in the newborn which could lead to neurodevelopmental problems [39][40][41]. The study found cases of separation from the newborn for up to 3 days after birth complications.…”
Section: Discussionmentioning
confidence: 96%
“…Separation between the mother and the newborn may create insecurity and unnecessary worrying for the mother and delay the bonding and breastfeeding initiation. Studies have also revealed separation as a cause for stressors in the newborn which could lead to neurodevelopmental problems [39][40][41]. The study found cases of separation from the newborn for up to 3 days after birth complications.…”
Section: Discussionmentioning
confidence: 96%
“…This research's results show that pain was significantly more common among mothers who had their newborn hospitalized in other units (nursery or neonatal ICU) and needed to move to follow their children, which may be related to this higher mobility or to the emotional overload of having their newborn in a different unit. Studies indicate that the process of mother-baby separation due to prematurity or newborn complications in the immediate postpartum period makes the mother feel fear, anxiety, insecurity, and distress (16)(17) , emotions which may negatively influence the perception of pain. In these situations, nurses should act as facilitators of skin-to-skin contact as soon as possible, fostering the bond between mother and baby (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the process of mother-baby separation due to prematurity or newborn complications in the immediate postpartum period makes the mother feel fear, anxiety, insecurity, and distress (16)(17) , emotions which may negatively influence the perception of pain. In these situations, nurses should act as facilitators of skin-to-skin contact as soon as possible, fostering the bond between mother and baby (16) .…”
Section: Discussionmentioning
confidence: 99%
“…É possível que, pelo fato de o bebê ter nascido a termo e, provavelmente não ter intercorrências durante a gestação, não esperavam que o bebê tivesse problemas de saúde que justificasse sua internação em UITN. Manzo et al (2018) apontaram que a internação pode desencadear diversos sentimentos negativos (frustração, tristeza, angústias, medo da perda seu filho e intensa preocupação frente ao desconhecido). Por outro lado, mesmo diante desses sentimentos negativos quando existe a presença do acompanhante em todo período de internação esse processo é vivenciado de forma menos traumática.…”
Section: Discussionunclassified
“…Contudo, não basta que os objetivos das políticas públicas de humanização sejam propostos, é necessário que as equipes compreendam sua importância e a efetivem. Para Manzo et al (2018), apesar das diversas políticas públicas propostas pelo Ministério da Saúde, com o objetivo de reduzir a morbimortalidade materna e do bebê, de modo a garantir a qualidade e humanização na assistência durante o parto e puerpério, ainda existem práticas que contradizem essas propostas.…”
Section: Introductionunclassified